The Casein Kinase 2‐Dependent Phosphorylation of NS5A Domain 3 from Hepatitis C Virus Followed by Time‐Resolved NMR Spectroscopy. (26th January 2016) - Secci, Erica; Luchinat, Enrico; Banci, Lucia
Abstract: Hepatitis C virus (HCV) chronically affects millions of individuals worldwide. The HCV nonstructural protein 5A (NS5A) plays a critical role in the viral assembly pathway. Domain 3 (D3) of NS5A is an unstructured polypeptide responsible for the interaction with the core particle assembly structure. Casein kinase 2 (CK2) phosphorylates NS5A‐D3 at multiple sites that have mostly been predicted and only observed indirectly. In order to identify the CK2‐dependent phosphorylation sites, we monitored the reaction between NS5A‐D3 and CK2 in vitro by time‐resolved NMR. We unambiguously identified four serine residues as substrates of CK2. The apparent rate constant for each site was determined from the reaction curves. Ser408 was quickly phosphorylated, whereas the three other serine residues reacted more slowly. These results provide a starting point from which to elucidate the role of phosphorylation in the mechanisms of viral assembly—and in the modulation of the viral activity—at the molecular level. Abstract : Phosphorylation in viral assembly mechanisms : CK2‐dependent phosphorylation of domain 3 of the NS5A protein from hepatitis C virus is critical for the virus assembly pathway. Time‐resolved NMR is the ideal technique with which to monitor multiple phosphorylation reactions. Four phosphorylation sites that react with different rates have been identified.